Can landscape characteristics help explain the different trends of Cantabrian brown bear subpopulations? - Lamamy, Cindy; Bombieri, Giulia; Zarzo-Arias, Alejandra; González-Bernardo, Enrique; Penteriani, Vincenzo (Mammal Research, 2019)
A central challenge in animal conservation is to understand how a population may respond to different habitat characteristics, which may affect their growth and viability. At the beginning of the twentieth century, the Cantabrian brown bear Ursus arctos population (north-western Spain) was separated into western and eastern subpopulations. Today, brown bears in the Cantabrian Mountains are recovering and the two subpopulations are reconnected. However, the western portion of the population represents ca. 90% of the entire population, the number of females with cubs-of-the-year has also shown a more rapid increase in the western subpopulation than in the eastern one and mean litter size is significantly larger in the west. By comparing the characteristics of the landscape used by brown bears in the western vs. eastern sectors of the population, we intended highlighting focal elements of landscape composition and structure that may help explain the differences in numbers and fecundity of these two subpopulations. We suggest that habitat use alone might not have the expected role in potentially explaining differences between subpopulations. Both the current positive trend of the Cantabrian population and our results seem to show that the dynamics affecting these subpopulations might be more complex than previously believed and cannot be understood on the basis of habitat analyses only. Suspicions may arise around direct human influences (e.g. persistence of poaching and/or bad practices during hunting) on the different trends exhibited by the two sectors of this endangered bear population. During this research, V.P. was financially supported by the Excellence Project CGL2017-82782-P financed by the Spanish Ministry of Science, Innovation and Universities, the Agencia Estatal de Investigación (AEI) and the Fondo Europeo de Desarrollo Regional (FEDER, EU). V.P. was also funded by a GRUPIN research grant from the Regional Government of Asturias (Ref.: IDI/2018/000151). G.B. was financially supported by a ...